Model Problem Based Learning (PBL) dalam Pembelajaran Pendidikan Agama Islam di Darul Muhmin School, Satun, Thailand - Pujiono, Tri; Hafriani, Rizka (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
Islamic Education plays a vital role in shaping students' character and moral values. One instructional strategy that fosters students’ comprehension and critical thinking skills is the Problem Based Learning (PBL) model. This study aims to examine the implementation strategy of PBL in Islamic Education at Darul Muhmin School, Satun, Thailand, and to analyze its impact on students’ understanding. Employing a qualitative approach, the research was conducted through direct field observations at the study site. The findings reveal that PBL effectively enhances students’ active engagement in the learning process, cultivates critical thinking and problem-solving abilities within the framework of Islamic values, and bridges theoretical concepts with practical applications through real-life experiences. The study concludes that the PBL model is a highly effective pedagogical approach for improving the overall quality of Islamic Education by integrating cognitive and moral development.